A Strategy to Use the Similes in Child's Environment to Teach the Letters in Kindergarten and Elementary School - Ali A. Al-Jafar (Sultan Qaboos University, 2016)
The study suggested a new strategy to teach the letters of Arabic to preschool children using similes from the local environment. It was assumed that the simile embodied the child's cultural experience, being a simple form of the image culture that shaped his or her identity. The study sample included one hundred and two children with an age range between 3 and 6 years, in Kuwait. The author identified the experiences taught in the preschool stage and chose those ones that were related to the cooperative society, and then asked every child to recall a name of anything in the society that begins with one of the twentyeightArabic letters. The author, then, asked every child a question about all the similes that he or she could deduce from the image of the letter, using the experience of "My House" as a model. Based on the similes that were obtained from the children, an integrated story demonstrating all Arabic letters was constructed. Consequently, using the suggested strategy to teach letters to the preschool and elementary school children was recommended.